"I had been given the space to grow": An innovative model of assessment in subject English in New South Wales, Australia. Issue 2 (7th September 2015) - Manuel, Jackie; Carter, Don
Abstract : Purpose: – This paper aims to provide a critical interpretative analysis of an innovative model of assessment in subject English in New South Wales, Australia. The purpose of this paper is to explore the theoretical and practical dimensions of assessment in the English Extension 2 course. This course forms part of suite of senior secondary English courses within the Higher School Certificate program that includes high-stakes external examination. Design/methodology/approach: – The paper draws on methods of documentary analysis. It sits within the tradition of curriculum research that critiques pre-active curriculum documents as a primary source for interpreting the theoretical and pedagogical principles and assumptions encoded in such documents. A social constructionist approach informs the analysis. Findings: – The model of assessment in the New South Wales (NSW) English Extension 2 course provides students with the opportunity to engage in sustained research and the production of a major piece of work. In its emphasis on student creativity, reflective practice, metacognition and independent research, the course exemplifies the ways in which the principle of assessing both process and product as organic is achievable in a context of high-stakes external examinations. Originality/value: – In an era of high-stakes, external and standardised testing regimes, this paper challenges the normative definitions of assessment prevalent in secondary schools, particularly at the senior secondary level. The assessment model underpinning the NSW English Extension 2 course offers a robust alternative to the increasingly prescriptive models evident in current education policy and practice. The paper calls for renewed attention to the potential for such a model of authentic assessment to be considered in the assessment programs of other subjects constituting the curriculum.